GMOS, GMMS DAN KEANEKARAGAMAN HAYATI INDONESIA - Santoso, Untung (Jurnal Bestari, 2001)
An increasing number of population is related to the increasing number of need of food. It is actually followed by farmland being residence. The demand of food production also adds, on the contrary, the facility does not support it. Once, pest and plant disease, environmental flaw, and pollution might obscure. Thus as proof, biotechnology can assist the food production progress and others above the former product rate through an assembly technology of GMOs and GMMs. This technology is dependant on potency of biological varieties that are source of various genes. Its careless application will have damaged and broken the biological varieties. The wisdom and carefulness of this application is needed to